Deskripsi Representasi Grafik Fungsi Trigonometri Mahasiswa Berbantuan Media Geogebra - Mohammad Archi Maulyda; Erry Hidayanto; Swasono Rahardjo (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This descriptive qualitative research aims to describe the form of mathematical representation that arises when students understand the relationship between changes in the coefficient of trigonometric functions with their graphical functions through GeoGebra media. Students in a class of 30 students are selected as research subjects and given a Student Worksheet. From the results of the student's work, it can be seen that there are 3 types of the tendency of representation that are used by students to complete Worksheets. Of the 3 types of trends, each student is taken 1 person who will further discuss the results of his work randomly because it is considered to represent the work of other students. The results showed that students represented Geogebra's appearance in 3 forms namely verbal representation, mathematical expression representation, and visual representation.Abstrak: Tujuan penelitian kualitatif deskriptif adalah untuk mendeskripsikan bentuk representasi matematis yang muncul ketika mahasiswa memahami hubungan antara perubahan koefisien fungsi trigonometri dengan grafik fugsinya lewat media GeoGebra. Mahasiswa dalam satu kelas yang berjumlah 30 mahasiswa dipilih sebagai subjek penelitian dan diberikan Lembar Kerja Mahasiswa. Dari hasil pekerjaan mahasiswa tersebut, terlihat ada tiga tipe kecenderungan bentuk representasi yang digunakan mahasiswa untuk menyelesaikan Lembar Kerja. Dari tiga tipe kecenderungan tersebut masing-masing diambil satu mahasiswa yang akan dibahas lebih lanjut hasil pekerjaanya secara random karena dinilai dapat mewakili hasil pekerjaan mahasiswa yang lain. Hasil penelitian menunjukan bahwa mahasiswa merepresentasikan tampilan Geogebra dalam tiga bentuk, yakni representasi verbal, representasi ekpresi matematis, dan representasi visual.